Online Fatwas in Pakistan using Social Networking Platforms - Samiullah Adel; Muhammad Numan (Ulumuna, 2023)
In the era of digital communications, religious dialogues have experienced significant transformations, notably with the rise of online fatwas via social media platforms. The spread of these digital religious verdicts has broadened the dissemination of information and public engagement while challenging traditional boundaries of freedom of speech. This research, grounded in the context of Pakistan, explores the implications and effectiveness of online fatwas. Through a qualitative approach, this study examines various social media platforms widely used in Pakistan to deliver online fatwas. The findings of this study suggest that these platforms have democratized religious discourse, shifting it from physical, sacred spaces such as mosques to the digital sphere. Furthermore, these platforms significantly influence individual beliefs, societal norms, and behaviors, thereby contributing to shifts in socio-political structures. Given the powerful influence of these platforms, the need for vigilant scrutiny and regulation is underscored. This study, therefore, offers critical insights into the digital transformation of religious practices and its vast implications for societal structures and individual behaviors. The conclusions drawn from this research could guide the management and dissemination of online fatwas, ensuring a balanced and beneficial societal impact.